Phylogeny of Yellow Fever Virus, Uganda, 2016 - Hughes, Holly R.; Kayiwa, John; Mossel, Eric C.; Lutwama, Julius; Staples, J. Erin; Lambert, Amy J. (Emerging infectious diseases, 2018)
In April 2016, a yellow fever outbreak was detected in Uganda. Removal of contaminating ribosomal RNA in a clinical sample improved the sensitivity of next-generation sequencing. Molecular analyses determined the Uganda yellow fever outbreak was distinct from the concurrent yellow fever outbreak in Angola, improving our understanding of yellow fever epidemiology.